1998
DOI: 10.1046/j.1365-2125.1998.00776.x
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine based measures of CYP1A2 activity correlate with oral clearance of tacrine in patients with Alzheimer's disease

Abstract: Aims  To study the potential utility of caffeine based probes of CYP1A2 enzyme activity in predicting the pharmokinetics of tacrine in patients with Alzheimer's disease. Methods  The pharmokinetics of a single 40 mg oral dose of tacrine were measured in 19 patients with Alzheimer's disease. Each patient also received 2 mg kg−1 [13C‐3‐methyl] caffeine orally and had breath and urine samples collected. Results  Tacrine oral clearance (CL F−1 kg−1 ), which varied 15‐fold among the patients, correlated signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…In fact, the apparent oral clearance of tacrine also correlated with the plasma caffeine metabolic ratio, but only in the second study period. These results corroborate the findings of Fontana et al [ 29], and further support a role of CYP1A2 in tacrine metabolism. Although statistically significant, the low degree of correlation between tacrine clearance and measures of CYP1A2 activity may be explained by the known intraindividual variation in CYP1A2 over time.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In fact, the apparent oral clearance of tacrine also correlated with the plasma caffeine metabolic ratio, but only in the second study period. These results corroborate the findings of Fontana et al [ 29], and further support a role of CYP1A2 in tacrine metabolism. Although statistically significant, the low degree of correlation between tacrine clearance and measures of CYP1A2 activity may be explained by the known intraindividual variation in CYP1A2 over time.…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, the caffeine breath test has been shown to correlate with the logarithm of the steady‐state plasma tacrine concentration [ 28]. While the present study was in progress, Fontana et al [ 29] published a study on the utility of caffeine based probes of CYP1A2 activity in predicting the pharmacokinetics of tacrine in 19 patients with Alzheimer’s disease. The caffeine breath test and two urinary caffeine metabolic ratios were shown to correlate with tacrine oral clearance.…”
Section: Discussionmentioning
confidence: 92%
“…The coadministration of echinacea and theophylline may result in an increased incidence of toxicity resulting from increased serum theophylline concentrations. Other CYP1A2 substrates that have adverse‐effect issues, such as cyclobenzaprine, tacrine, and clozapine, may be affected by echinacea coadministration 62 , 63 , 64 , 65 , 66 , 67…”
Section: Discussionmentioning
confidence: 99%
“…Population studies of patients with amyotrophic lateral sclerosis also showed 32% lower clearance in women compared with men 73 . Breath test phenotyping with caffeine correlated with oral clearance of tacrine, a CYP1A substrate, in patients with Alzheimer's disease, but sex differences were not detected 74 . Ethnic polymorphic differences may also confound sex effects as shown by observations of sex differences found only in Chinese for phenacetin clearance 75 …”
Section: Pharmacokinetic Changes With Aging and Differences Between Mmentioning
confidence: 99%